Kinesiophobia Severity Categories and Clinically Meaningful Symptom Change in Persons With Achilles Tendinopathy in a Cross-Sectional Study: Implications for Assessment and Willingness to Exercise - Chimenti, Ruth L.; Post, Andrew A.; Silbernagel, Karin Grävare; Hadlandsmyth, Katherine; Sluka, Kathleen A.; Moseley, G. Lorimer; Rio, Ebonie (Frontiers in Pain Research, 2021)
Objectives: 1) Validate thresholds for minimal, low, moderate, and high fear of movement on the 11-item Tampa Scale of Kinesiophobia (TSK-11), and 2) Establish a patient-driven minimal clinically important difference (MCID) for Achilles tendinopathy (AT) symptoms of movement-evoked pain and stiffness. Methods: Responses from 442 adults with chronic AT to a public online survey were analyzed. Kinesiophobia subgroups (Minimal ≤ 22, Low 23–28, Moderate 29–35, High ≥ 36 scores on the TSK-11), pain MCID subgroups (10-, 20-, 30-, >30-points on a 0 to 100-point scale), and stiffness MCID subgroups (5, 10, 20, >20 min) were described as median [interquartile range] and compared using non-parametric statistics. Results: Subgroups with higher kinesiophobia reported were less likely to complete 3 heel raises (Minimal = 93%, Low = 74%, Moderate = 58%, High = 24%). Higher kinesiophobia was associated with higher expected pain (Minimal = 20.0 [9.3–40.0], Low = 43.0 [20.0–60.0], Moderate = 50.0[24.0–64.0], High = 60.5[41.3–71.0]) yet not with movement-evoked pain (Minimal = 25.0 [5.0–43.0], Low = 31.0 [18.0–59.0], Moderate = 35.0 [20.0–60.0], High = 43.0 [24.0–65.3]). The most common movement-evoked pain MCID was 10 points (39% of respondents). Half of respondents considered a 5-min (35% of sample) or 10-min (16%) decrease in morning stiffness as clinically meaningful. Conclusions: Kinesiophobia likely contributes to willingness to complete an activity but not necessarily to the magnitude of movement-evoked pain. Most participants indicated that reducing their pain severity to the mild range would be clinically meaningful.